Growth haematology and organ histopathology in broilers fed raw and processed velvet bean-based diets (2006)
Velvet beans (Mucuna pruriens) is currently being promoted as food for man and feed for animals in Nigeria. Its potential and implication as alternative plant protein was studied with one hundred and eight l-d-old Anak broiler chicks. Raw and heated Mucuna bean meals (RMBM & HMBM respectively) were used to replace soybean meal (SBM) and to assess the effect on performance, hislopathological changes and haematology in broiler starters and finishers. Three diets were formulated. Diet I was the basal diet and contained 120g kg-1 SBM while diets 2 and 3 contained 120 g kg 1 HMBM and RMBM respectively in place of SBM. Each diet had 3 groups of 12 birds each. Feed intake, FCR and weight gain in birds on the RMBM and HMBM diets were significantly (p < 0.05) depressed compared to birds on the SBM diet at the starter phase but not at the finisher phase for the HMBM diet but on both phases forr the RMBM diet. The packed cell volume (PCV), haemoglobin (Hb), red blood cell count (RBC) and while blood cells (WBC) were significantly (p < 0.05) reduced in the RMBM diets compared to the other 2 diets. Histopathological results showed that birds on the RMBM diet showed severe and widespread vacuolar degeneration and necrosis of the hepatocytes interstitial congestion, tubular degenerations and necrosis in the kidneys. The hearts in birds on the RMBM diet had degeneration and fragmentation of their myofibrils and lymphoid depopulation in the spleen. These results suggest the possibility if utilising Mucuna bean meal to replace soybean meal in broiler feeding at both starter and finisher phases only when subjected to heat treatment. Thus, in spite of its present promotion as food for man and feed for animals in the country, the bean should be subjected to appropriate processing to overcome its depressive effects on feed intake, growth and degenerative syndromes in organs.